TANGGUNG JAWAB INFLUENCER ATAS KASUS ENDORSEMENT PRODUK PALSU DALAM UPAYA PERLINDUNGAN KONSUMEN - Rista Yuliani (2022)
This study aims to analyze the responsibility of influencers to consumers regarding cases of endorsement of counterfeit products based on the UUPK and legal remedies that can be taken by consumers who are harmed by buying and selling fake products due to influencer reviews on social media. The method used in this research is normative juridical with a statutory approach (Statute Approach) and a case approach (Case Approach). The results of the study show that influencers have civil and criminal responsibilities, where consumers who feel aggrieved can ask for compensation in the form of refunds or replacement of goods and/or services of similar or equivalent value, or health care and/or compensation. If there are consumers who suffer losses caused by business actors, the rule of law has provided a way for consumers to fight for their rights that have been violated both civilly and criminally. However, in this case, it requires the awareness of every consumer to actively defend their rights so that they are not violated by business actors who commit fraud when selling their products through online media.